The reality of using artificial intelligence applications in the educational process from the point of view of female educational rehabilitation students at Sohar University - Alabri, Fatma Khalfan (Journal of Curriculum and Teaching Methodology, 2024)
The study aimed to reveal the reality of using artificial intelligence applications in the educational process from the point of view of female educational qualification students at Sohar University. The researcher followed the descriptive approach using a questionnaire distributed to female educational qualification students in scientific specializations, numbering (35). The results showed that the general arithmetic mean of the responses of female educational qualification students in the first field obtained an average of (1.91 out of 3), while the obstacles that limit their use of artificial intelligence applications obtained an average of (2.03 out of 3), both with a rating of (high). The results of the study also showed that there were no statistically significant differences at the level of (α≤0.05) in the averages of the sample’s responses to the questionnaire fields attributed to the variables (age, training courses. She also suggested more research and directing attention towards artificial intelligence applications and their employment in educational institutions.